2013
DOI: 10.1371/journal.pone.0071977
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Domestic Water Consumption in Rural Households upon Access to Improved Water Supply: Insights from the Wei River Basin, China

Abstract: Comprehensively understanding water consumption behavior is necessary to design efficient and effective water use strategies. Despite global efforts to identify the factors that affect domestic water consumption, those related to domestic water use in rural regions have not been sufficiently studied, particularly in villages that have gained access to improved water supply. To address this gap, we investigated 247 households in eight villages in the Wei River Basin where three types of improved water supply sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 31 publications
6
40
0
3
Order By: Relevance
“…This inverse relationship between per capita water consumption and household size is consistent with studies by Martin (1999) and Keshavarzi et al (2006) who demonstrated in their studies that percapita water consumption in large families was lower compared to smaller families because the use of water for domestic activities such as home cleaning, gardening, taking care of livestock were relatively independent of family size (Fan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This inverse relationship between per capita water consumption and household size is consistent with studies by Martin (1999) and Keshavarzi et al (2006) who demonstrated in their studies that percapita water consumption in large families was lower compared to smaller families because the use of water for domestic activities such as home cleaning, gardening, taking care of livestock were relatively independent of family size (Fan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…The low explanatory power in this study was consistent with other studies of domestic water use in Mexico which found an R 2 of 0.13 (Corral-Verdugo et al, 2002), 0.22 for a study conducted in Australia (Syme et al, 2004), and 0.37 for another conducted in rural China (Fan et al, 2013). The results from our research therefore suggests that percapita domestic water consumption in households with children less than five years may be influenced by varied factors which necessitates further exploration.…”
Section: Discussionsupporting
confidence: 82%
“…The area of rural residential land increased by 100,000 ha, and the rural residential land per capita increased from 193 m 2 to 230 m 2 from 1996 to 2008 [17]. Meanwhile, a large number of the rural population is migrating to urban, with more than 120 million migrants per year in China [17,18]. These migrants possess residential and cultivated land in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…As the household size increases, the average consumption of a member of a family decreases (Fan, et al, 2013). The decrease in per capita consumption as the number of household members increases is attributed to the sharing of water needs in cooking and washing clothes, dishes, and cars.…”
Section: Issn: 2320-5407mentioning
confidence: 99%